Effect of high dose folic acid supplementation in pregnancy on pre-eclampsia (FACT): double blind, phase III, randomised controlled, international, multicentre trial - Wen, Shi Wu (BMJ, 2018)
OBJECTIVE: To determine the efficacy of high dose folic acid supplementation for prevention of pre-eclampsia in women with at least one risk factor: pre-existing hypertension, prepregnancy diabetes (type 1 or 2), twin pregnancy, pre-eclampsia in a previous pregnancy, or body mass index ≥35. DESIGN: Randomised, phase III, double blinded international, multicentre clinical trial. SETTING: 70 obstetrical centres in five countries (Argentina, Australia, Canada, Jamaica, and UK). PARTICIPANTS: 2464 pregnant women with at least one high risk factor for pre-eclampsia were randomised between 2011 and 2015 (1144 to the folic acid group and 1157 to the placebo group); 2301 were included in the intention to treat analyses. INTERVENTION: Eligible women were randomised to receive either daily high dose folic acid (four 1.0 mg oral tablets) or placebo from eight weeks of gestation to the end of week 16 of gestation until delivery. Clinicians, participants, adjudicators, and study staff were masked to study treatment allocation. MAIN OUTCOME MEASURE: The primary outcome was pre-eclampsia, defined as hypertension presenting after 20 weeks’ gestation with major proteinuria or HELLP syndrome (haemolysis, elevated liver enzymes, low platelets). RESULTS: Pre-eclampsia occurred in 169/1144 (14.8%) women in the folic acid group and 156/1157 (13.5%) in the placebo group (relative risk 1.10, 95% confidence interval 0.90 to 1.34; P=0.37). There was no evidence of differences between the groups for any other adverse maternal or neonatal outcomes. CONCLUSION: Supplementation with 4.0 mg/day folic acid beyond the first trimester does not prevent pre-eclampsia in women at high risk for this condition. TRIAL REGISTRATION: Current Controlled Trials ISRCTN23781770 and ClinicalTrials.gov NCT01355159.